Serologic test vs antigenemia assay as diagnostic marker for cytomegalovirus infection in children. - Agnes Yunie, Agnes Yunie (Universitas Gadjah Mada, 2002)
Objective: To determine the level IgG and IgM anti-CMV in children clinically suspected to be infected by Cytomegalovirus (CMV) and to determine the diagnostic value of IgG dan IgM anti-CMV as diagnostic tools for active CMV infection with antigenemia assay as the gold standard.Material and methods: Diagnostic test, observational cross sectional study. All children suspected to have CMV infection who were hospitalized or who visited neurology outpatient clinic in Sardjito Hospital in March 1